Answer:
Step-by-step explanation: 6z=-2-10
6z= -12
z=-12/6
then z= -2
Answer:
A: The coefficient changes from 120 to 117, and the base changes from 1.033 to 1.035. The function that represents the second model is A(t)=117(1.035)^t.
Step-by-step explanation:
luxury tax you get only the amount that you need
Answer:
m = x+y-z
Step-by-step explanation:
Given the expression.
(a^x a ^y) ÷ a^z = a^m
We are to express m in terms of x, y and z.
Using the multiplicative law of indices, the expression becomes:
a^{x+y} ÷ a^z = a^m
Applying the division rule in indices
a^{x+y} ÷ a^z = a^{x+y-z}
The equation becomes
a^{x+y-z} = a^m
Cancel out the base and equate the powers as shown:
x+y-z = m
Hence the expression of m in terms of x, y and z is m = x+y-z
Answer:
6509.84 ft to the nearest hundredth.
Step-by-step explanation:
We have a right triangle in which the opposite side is 1479 ft and we need to find the adjacent side:
Tan 12.8 = opposite / adjacent side
tan 12.8 = 1479/ x
x = 1479/tan 12.8
= 6509.84 ft.